Pemberdayaan Remaja Masjid Melalui Revitalisasi Kepengurusandi Masjid Al-Huda Kota Batu - Shafina Shalsabila; Eka Ismi Nadifah; Muhammad Misbachul Munir; Khisna Azizah; Akhmad said (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2025)
Abstract The mosque functions as a central hub for Muslim worship and social activities. It plays a strategic role in community development, particularly in nurturing the younger generation as prospective future leaders. However, for more than 27 years, Al-Huda Mosque in Batu City located in Junrejo District, Dadaprejo Village experienced a vacancy in the management of the mosque youth organization (Remaja Masjid/Remas), with all activities being handled entirely by the takmir (mosque management board). This community service program employed a Participatory Action Research (PAR) approach, involving collaborative planning, action, observation, and reflection with local stakeholders. The program resulted in the revitalization of the mosque youth organization, increased youth participation, and the establishment of sustainable mosque activities. This initiative fosters leadership regeneration and social change by emphasizing participatory strategies to revive a previously inactive religious youth organization. Keywords: Empowerment, Mosque Youth Organization, Management Revitalization. Abstrak Masjid berfungsi sebagai pusat utama bagi ibadah muslim dan kegiatan sosial. Memiliki peran strategis dalam pengembangan komunitas, khususnya dalam membina generasi muda sebagai calon pemimpin masa depan. Namun, ternyata selama kurun waktu lebih dari 27 tahun, Masjid Al-Huda di Kota Batu kecamatan Junrejo, kelurahan Dadaprejo ini mengalami kekosongan dalam pengelolaan remaja masjid (Remas), dan seluruh kegiatan ditangani sepenuhnya oleh pengurus takmir. Pengabdian ini menggunakan pendekatan Participatory Action Research (PAR), program ini melibatkan perencanaan, aksi, observasi, dan refleksi secara kolaboratif dengan para pemangku kepentingan lokal. Program ini menghasilkan reformasi Remas, peningkatan partisipasi remaja, dan kegiatan masjid yang berkelanjutan. Inisiatif ini mendorong regenerasi kepemimpinan dan perubahan sosial, dengan menekankan strategi partisipatif untuk menghidupkan kembali organisasi remaja keagamaan yang sempat vakum. Kata Kunci: Pemberdayaan, Remaja Masjid, Revitalisasi Kepengurusan.